A review on the green synthesis of nanoparticles for energy conversion and storage (Kuwait Journal of Science)
Green synthesis is an important approach to circumvent environmental hazards and provide sustainable energy while achieving reduction in energy consumption and production cost. Green synthesized MnO2 NPs, TiO2 NPs, and CuO NPs-based electrodes have been known to exhibit high specific capacitance, ranging from 61 to 139 Fg-1, 105 to 224 Fg-1, and 176–328 F g−1 for energy storage in supercapacitors. Moreover, a range from 275 to 699 mAh g−1 discharge capacity has been reported using facile green synthesized Co3V2O8 NPs as electrode material for lithium-ion batteries. Hydrogen as a clean fuel has been notably generated with a high amount of evolution ranging from 268.9 to 310.7 μmolg−1 via water splitting using green-synthesized Co3O4 NPs. Comparatively, biogenic Pt-based nanocomposite for fuel cells have been shown to generate higher current density (5.43 mA cm−2) than conventionally synthesized Pt nanocubes (0.9 mA cm−2) and Pt nanoflowers (2.8 mA cm−2). Future studies should focus on addressing challenges such as the high variability in morphological properties, low conversion rates, and poor yields commonly associated with green synthesized nanoparticles, as these factors significantly affect their energy conversion and storage applications. In comparison to previous studies, a deeper understanding of the efficiency of green synthesized nanoparticles in energy conversion and storage has been accentuated, aiming to contribute to solution for the ongoing global energy shortages. © 2025 The Author